A small-scale ochratoxin A production method for rapid and affordable assay for screening microorganisms for their ability to degrade the mycotoxin. (15th February 2022) - Corrêa, Jessica Audrey Feijó; Nazareth, Tiago de Melo; Meca, Giuseppe; Luciano, Fernando Bittencourt
Abstract: The use of biological agents able to metabolize mycotoxins to non-toxic compounds is a strategy that has received growing interest. However, the high costs of laborious methods for identifying potential candidates are obstacles for new products development. Thereon, our objective was to establish a rapid and affordable bacterial screening assay for ochratoxin A (OTA) biodegradation, based on a small-scale OTA production method to replace the use of mycotoxin standards, aiming to reduce costs. Aspergillus strains were assessed in liquid and solid matrices. A. sclerotioniger CECT 20583 produced the highest OTA levels, 850 μL/L in liquid (day 7) and 5273 μL/kg in solid (day 35). The liquid system was prioritized since the method obtained higher recovery and reproducibility. To verify the applicability, 107 bacterial isolates were screened using microtubes (500 μL of filtered OTA solution + 400 μL of tryptic soy broth (TSB) + 100 μL of inoculum, 24 h incubation). Nineteen isolates showed decontaminating potential, enabling the dismission of more than 80% of initial candidates. In short, the proposed assay requires little time and investment to get information from isolates on their capability of degrading OTA, saving resources for further research stages. Highlights: Most of the evaluated ochratoxin A (OTA) production methods were prolific. High concentrations of OTA were achieved in both liquid and solid matrices. The proposed assay can provide information on isolates potential within 2 weeks. The treatment with 19 isolates resulted in more than 30% OTA reductions.